Evaluation of the Reasoning and Rehabilitation Cognitive Skills Development Program Implemented in Juvenile Intensive Supervision Probation in Colorado, 1994-1995 - Pullen, Suzanne ([Verlag nicht ermittelbar], 1999)
This study was a program evaluation of the Reasoning and Rehabilitation Cognitive Skills Development Program, an educational program that taught cognitive skills to offenders, as implemented in juvenile intensive supervision probation in Colorado. Using an experimental design, researchers sought to measure the extent of change in attitudes and behaviors due to the cognitive skills program by administering pre- and post-test interviews. Researchers also measured recidivism by conducting interviews with probation officers who supervised the offenders in the sample six months after termination from intensive supervision. These interviews were supplemented with administrative records data that provided background information about the sample. In addition, administrative data were collected on all juveniles sentenced to intensive supervision during fiscal years 1994 and 1995 to compare juveniles in the sample with all juveniles in the intensive program. Variables in this collection include cognitive measures, such as impulsivity, problem-solving ability, egocentricity, and cognitive style. Other variables measure emotional responses to various situations, attitudes toward the law, values, drug abuse, program participation, and recidivism. Administrative data include age, gender, ethnicity, offense of conviction, and basic assessment data.